1995
DOI: 10.1083/jcb.131.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface-bound elastase and cathepsin G on human neutrophils: a novel, non-oxidative mechanism by which neutrophils focus and preserve catalytic activity of serine proteinases.

Abstract: Abstract. Serine proteinases of human polymorphonuclear neutrophils play an important role in neutrophilmediated proteolytic events; however, the non-oxidative mechanisms by which the cells can degrade extracellular matrix in the presence of proteinase inhibitors have not been elucidated. Herein, we provide the first report that human neutrophils express persistently active cell surface-bound human leukocyte elastase and cathepsin G on their cell surface. Unstimulated neutrophils have minimal cell surface expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
322
1
3

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(340 citation statements)
references
References 71 publications
(74 reference statements)
14
322
1
3
Order By: Relevance
“…These studies are compatible with the results of a recent study describing the binding of elastase to the neutrophil plasma membrane [24]. The studies by OWEN et al [25] showed the importance of surface-bound elastase and of the pericellular environment in determining the enzymatic activity of elastase in tissues.…”
Section: Immunocytochemical Localization Of Neutrophil Elastasesupporting
confidence: 89%
“…These studies are compatible with the results of a recent study describing the binding of elastase to the neutrophil plasma membrane [24]. The studies by OWEN et al [25] showed the importance of surface-bound elastase and of the pericellular environment in determining the enzymatic activity of elastase in tissues.…”
Section: Immunocytochemical Localization Of Neutrophil Elastasesupporting
confidence: 89%
“…Membrane-bound HLE exhibits striking catalytic activity against fibronectin and type IV collagen [49,80], indicating that this form of the enzyme may play important roles in penetration of tissue barriers during cellular migration. Membrane-bound CG has potent capacity to convert the biologically inactive peptide angiotensin I to angiotensin II [81], which regulates vascular smooth muscle tone, vascular permeability, and mononuclear cell chemotaxis.…”
Section: Membrane Bindingmentioning
confidence: 99%
“…In marked contrast to HLE and CG that are freely released from leukocytes, membrane-bound HLE and CG are remarkably resistant to inhibition by naturally occurring proteinase inhibitors [80,81]. It is noteworthy that membrane-bound CG can convert angiotensin I to angiotensin II even in undiluted plasma [81].…”
Section: Membrane Binding Of Proteinasesmentioning
confidence: 99%
See 2 more Smart Citations